2015
DOI: 10.1017/s2071832200021040
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Precedent: The Case Law of the European Court of Justice in Three Dimensions

Abstract: The case law of the Court of Justice of the European Union (CJEU) is one of the most important sources of European Union law. However, case law's role in EU law is not uniform. By empirically studying how the Court uses its own case law as a source of law, we explore the correlation between, on the one hand, the characteristics of a CJEU case—type of action, actors involved, and area of law—and, on the other hand, the judgment's “embeddedness” in previous case law and value as a precedent in subsequent cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The characteristics of the EU citation network have been described and discussed elsewhere (Derlén & Lindholm, 2014, 2015). Similar to the citation networks of the U.S. Supreme Court (Fowler, Johnson, Spriggs, Jeon, & Wahlbeck, 2007) and the ECtHR (Lupu & Voeten, 2012), most cases are cited by relatively few other cases, while a few cases are heavily cited.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the EU citation network have been described and discussed elsewhere (Derlén & Lindholm, 2014, 2015). Similar to the citation networks of the U.S. Supreme Court (Fowler, Johnson, Spriggs, Jeon, & Wahlbeck, 2007) and the ECtHR (Lupu & Voeten, 2012), most cases are cited by relatively few other cases, while a few cases are heavily cited.…”
Section: Methodsmentioning
confidence: 99%
“…In place of k − and k + above, we use Kleinberg's [51] authority and hub scores. These have been shown to accurately recover legallysignificant cases from CLCNs [2,3,5,40,52]. We denote authority and hub scores as A(k − ) and A(k + ) respectively.…”
Section: Authoritymentioning
confidence: 99%
“…Including 5 baselines, subject models, and alternative normalizations, a total of 16 different models are run for 50 iterations each. 5 To promote comparisons across models, we fix a few key parameters in our simulations. First, |N t | is fixed universally at 1.…”
Section: Model Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsson, Naurin, Derlén, & Lindholm, (2017) indicated that legal factors and more complex cases could increase the use of precedent. Meanwhile, Derlén & Lindholm (2015) discovered that the precedential power of a judgment is positively correlated to the number of cases.…”
Section: Introductionmentioning
confidence: 99%